Dunkirk - Holmes, Alex; Cumberbatch, Benedict, 1976-; Beale, Simon Russell; Dalton, Timothy, 1944- ([London] : BBC, 2017)
Follows the events of the maritime operation at Dunkirk in May 1940, when the British Navy rescued the British and French troops besieged by the Germans.
Retreat -- Evacuation -- Survival.
Dolby digital 2.0, anamorphic wide screen 1.78:1.
Features: Dunkirk : the final tribute.
Benedict Cumberbatch, Simon Russell Beale ; Timothy Dalton, narrator.
Originally broadcast on television in 2004.
TV rating: Not rated.
Closed-captioned.
Keywords: Dunkirk, Battle of, Dunkerque, France, 1940.; World War, 1939-1945 -- Personal narratives, English; World War, 1939-1945 -- Campaigns; World War, 1939-1945 -- Search and rescue operations; Dunkerque (France); Historical reenactments (Television programs); Historical television programs; Documentary television programs; Television mini-series.; Nonfiction television programs; Video recordings for the hearing impaired